Differences in state- and district-level stakeholders' perceptions of curriculum coherence and school impact in national curriculum reform. Issue 3 (11th April 2019) - Sullanmaa, Jenni; Pyhältö, Kirsi; Pietarinen, Janne; Soini, Tiina
Abstract : Purpose: Shared understandings of curriculum reform within and between the levels of the educational system are suggested to be crucial for the reform to take root. The purpose of this paper is to explore variation in perceived curriculum coherence and school impact among state- and district-level stakeholders. Design/methodology/approach: The participants ( n =666) included state- and district-level stakeholders involved in a national curriculum reform in Finland. Latent profile analysis was employed to identify profiles based on participants' perceptions of the core curriculum's coherence and the reform's impact on school development. Findings: Two profiles were identified: high coherence and impact, and lower consistency of the intended direction and impact. State-level stakeholders had higher odds of belonging to the high coherence and impact profile than their district-level counterparts. Practical implications: The results imply that more attention needs to be paid in developing a shared and coherent understanding particularly of the intended direction of the core curriculum as well as the reform's effects on school-level development among state- and district-level stakeholders. Originality/value: The study contributes to the literature on curriculum reform by shedding light on the variation in perceived curriculum coherence and school impact of those responsible for a large-scale national curriculum reform process at different levels of the educational system.